Management of Post-Traumatic Osteomyelitis in the Lower Limb: Current State of the Art - Chan, James K. K.; Ferguson, Jamie Y.; Scarborough, Matthew; McNally, Martin A.; Ramsden, Alex J. (Indian Journal of Plastic Surgery, 2019)
Osteomyelitis (OM) of the lower limb represents a large unmet global healthcare burden. It often arises from a contiguous focus of infection and is a recognized complication of open fractures or their surgical treatment, arthroplasty, and diabetic foot ulcers. Historically, this debilitating condition is associated with high rates of recurrence and secondary amputation. However, excellent long-term outcomes are now achieved by adopting a multidisciplinary approach with meticulous surgical debridement, skeletal and soft tissue reconstruction, and tailored antimicrobial treatment. This review focuses on the modern evidence-based management of post-traumatic OM in the lower limb from a reconstructive plastic surgery perspective, highlighting the latest developments and areas of controversy.
Keywords: osteomyelitis; soft tissue reconstruction; lower limb